Hubungan Karakteristik Petani dengan Perilaku Komunikasi Petani di Subak Umalayu Kelurahan Penatih Kecamatan Denpasar Timur - PASARIBU, MIKA DAMAYANTI; SUARDI, I DEWA PUTU OKA; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
The Relationship of Farmer Characteristics with Farmer Communication Behavior in Rice Cultivation in Subak Umalayu Penaturahan Village, East Denpasar District.  The lack of information sources from extension workers in Subak Umalayu has resulted in inadequate rice cultivation success. The research objective is to determine farmers characteristics, farmers communication behavior, and the relationship of the two. The types of data used in this research are primary and secondary data. This study uses quantitative descriptive method and Rank Spearman analysis. Based on the analysis, in terms of characteristic, the average age of farmers is 58 years old, most farmers’ education level is at junior high school, farmers’ average land ownership is 23.56 acres, farmers' average income is IDR 1,600,000, and the average farming experience of farmers is 20 years. In terms of communication behavior, Subak Umalayu farmers are quite good as reflected in each indicator, namely frequently looking for information on rice cultivation and frequently interacting within a group, but contact between farmers and extension workers / other parties is still rare and they rarely convey information on rice cultivation. Openness of farmers to the mass media is never classified. Based on the significance or sig- (2-tailed) value of the Spearman Rank correlation test, there is no significant relationship between farmer characteristics and farmer communication behavior. It is recommended to find information on rice cultivation, field PPL visits, and improvement of access to mass media in order to fulfill maximum information needs.